A rare case of caecal volvulus post gastrectomy for gastric cancer. (2020) - Diab, Jason; Bender, Kyle; Lorenzo, Aldenb; Merrett, Neil
Highlights: Gastric cancer and multiple comorbidities in an ageing population leads to a higher post-operative risk of complications. Post-operative complications can include intra operative damage to vessels and viscera, anastomotic leakage, and many more. Rare complications can occur when dealing with high risk surgical cases. Abstract: Introduction: Surgery for gastric cancer is associated with a high morbidity and mortality rate. Postoperative complications are not uncommon in this setting and an understanding of risk factors and patient profile can impact clinical outcomes. Presentation of case: We present a rare event where a 64 year old patient post gastrectomy for a T1 gastric carcinoma developed a caecal volvulus leading to critical instability. This demonstrates how two events can occur in time leading to critical instability. Exploratory laparotomy revealed a caecal volvulus that had obstructed the jejunostomy site. She had a right hemicolectomy and the jejunostomy was unkinked. This is the first documented case report of this type in the literature. Discussion: Surgical resection remains the cornerstone therapy for gastric cancer. Postoperative complications are not uncommon in this setting where risk factors impact clinical outcomes. The importance of risk factors has been demonstrated in patients who underwent gastrectomy. We present a rare event where a patient post gastrectomy develops a caecal volvulus demonstrating how two events can occur in time leading to critical instability. Conclusion: Post operative complications are not uncommon in gastrectomies. Although common things occur commonly, one must consider rare events when a patient significantly deteriorates.